Who Is Inclined to Hide the Truth: Evidence from Public Procurement. Issue 13 (2nd October 2020) - Yakovlev, Andrei; Tkachenko, Andrey; Rodionova, Yuliya
ABSTRACT: This paper presents a survey-based methodological approach to detect potential opportunism by counterparts who are linked with agents through contractual relations. The methodology proposes asking counterparts about attitudes toward some behaviors of agents, which are undesirable from the principal and benevolent counterpart perspective. The approach identifies the potential opportunism of counterparts based on the intensity with which they justify such behavior and provide unrealistic assessments of commonly known problems. The approach is especially important in a situation where the rules are inconsistent with reality and the principal can no longer disentangle the benevolent and opportunistic behavior of the agent. The authors test this approach by conducting a survey of procurers and suppliers of public procurement contracts in Russia.